Tindak Tutur Direktif Bahasa Arab dalam Film Ashabul Kahfi - Mahera, Intan Anisaul (Mahira: Journal of Arabic Studies, 2021)
This research is an Arabic directive speech act research in the film "Ashabul Kahfi". This study aims to describe the types of Arabic directive speech acts in the film "Ashabul Kahfi" and to describe the function of the directive speech acts. presentation of the results of data analysis. The data was collected by listening and recording the directive utterances contained in the film "Ashabul Kahfi". At the data analysis stage, a pragmatic approach with contextual methods was used. Then the presentation of the results of data analysis is done by informal methods. The results showed that the types of Arabic directive speech acts in the film "Ashabul Kahfi" were direct speech acts in the form of imperative sentences, indirect speech acts in the form of declarative sentences and interrogative sentences, and literal speech acts. The functions of the Arabic directive speech acts in the film "Ashabul Kahf" are: ordering, forbidding, asking, advising, inviting, expecting, warning, challenging and inviting.